2021
DOI: 10.4103/apjon.apjon-2097
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pain Self-Management Education on Pain Severity and Quality of Life in Metastatic Cancer Patients

Abstract: Objective: Proper pain control in cancer patients is one of the prime needs of metastatic cancer patients. It is, then, one of the essential objectives of health care workers. The present study aimed to pinpoint the impact of pain self-management education on the pain severity and the quality of life in patients with metastatic cancers using complementary medicine approaches. Methods: This clinical trial study was performed in the Oncology Specialty Clinic of Ahvaz Gole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Koller et al (2018) and Raphaelis et al (2020) demonstrated a noticeable decrease in average pain and worst pain intensity; however, minor effects between‐group differences were found during the study period. Musavi et al (2021) reported a significant difference between the pain intensity levels in the two groups from the second week after the intervention ( p < .0001).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Koller et al (2018) and Raphaelis et al (2020) demonstrated a noticeable decrease in average pain and worst pain intensity; however, minor effects between‐group differences were found during the study period. Musavi et al (2021) reported a significant difference between the pain intensity levels in the two groups from the second week after the intervention ( p < .0001).…”
Section: Resultsmentioning
confidence: 97%
“…Four studies usedQoL as a secondary outcome. They were assessed using the validated European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ C30)(Jahn et al, 2014;Musavi et al, 2021;Raphaelis et al, 2020) and a 12-item self-report tool(Koller et al, 2018). Two studies assessed patients' pain-related knowledge.F I G U R E 3 Risk of bias summary.…”
mentioning
confidence: 99%
“…Also nurse act as educators to the patient and family about how to use palliative treatment methods at home. 32 It is suggested that massage therapy is educated to nursing students with the aim of improving the quality of patients’ life during hospitalization. It can also improve patients’ satisfaction by improving their life quality and reduce re-admission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is the most effective treatment for cancer children [15]. Chemotherapy destroys neoplastic cells and even healthy cells since it does not have any differentiation between normal and neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%